Expression Française dalam Kepemanduan Wisata Overland - Ferhadius Endi; Pradnya Paramita Dewi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Expression Française (French expression) is an expression that is often used in tour guiding to create effective communication, as well as to show the tour guide's ability to speak French. This study aims to analyze the forms and meanings of the Expression Française found in overland trip. This research is a qualitative descriptive study through interview and direct observation, then the data is analyzed using the triangulation method. The results of this research shows that there are 14 forms of Expression Française which are fixed and in the courant and familier languages register. There are two types of meaning found in the Expression Française; opaque and transparent.